A comparative study of performance of AC and DC electric drive control systems with variable moment of inertia - Addasi E. Said; Abdullah M. Eial Awwad (Bulletin of Electrical Engineering and Informatics, 2021)
In electric drive control systems, the main goal is to maintain the driving motor speed to meet the mechanism’s requirements. In some practical industrial applications the mechanically-coupled load to the motor shaft has a varying mass during the system operation. Therefore, the change of mass changes the value of the moment of inertia of the system. The moment of inertia impacts the system operation, particularly the transient performance. Therefore, the variation of moment of inertia on the motor shaft during its operation creates additional challenges to accomplish a high-quality speed control. The main purpose of the current work is to study the impact of the variation of moment of inertia on the performance of both AC and DC electric drive control systems and to make a comparison between them. A mathematical analysis and simulations of the control system models had been presented; one time with three-phase induction motor and another time with DC motor, both with variable moment of inertia. A simulation of both systems had been accomplished using the Simulink software in MATLAB. The simulation results of operation of these systems have been analysed in order to get useful conclusions and recommendations for the electric drive control system designer.